(untitled) - Black, Rex (Indianapolis, IN, 2007)
Testing even a simple system can quickly turn into a potentially infinite task. Faced with tight costs and schedules, testers need to have a toolkit of practical techniques combined with hands-on experience and the right strategies in order to complete a successful project. World-renowned testing expert Rex Black provides you with the proven methods and concepts that test professionals must know. He presents you with the fundamental techniques for testing and clearly shows you how to select and apply successful strategies to test a system with budget and time constraints.
Keywords: Computer software,Computer software,Phần mềm máy tính,Phần mềm máy tính; Testing,Testing,Thử nghiệm,Thử nghiệm